Acute hemorrhage: approach to imaging with CTA - Md Ralib @ Md Raghib, Ahmad Razali (2011)
Multidetector CT (MDCT) had played a major role in the diagnosis of acute arterial haemorrhage. It has emerged as a modality of choice in the diagnosis of acute gastrointestinal hemorrhage, with the advantage of a faster scanning time, multiphase acquisition and wider anatomic coverage. Yoon et al had observed that the arterial phase MDCT depicted contrast extravasation in 21 of 26 patients. This gives MDCT a sensitivity, specificity, accuracy, and positive and negative predictive value of MDCT for detecting acute gastrointestinal hemorrhage of 90.9%, 99%, 97.6%, 95% and 98% respectively. They also showed that the location of contrast extravasation shown on MDCT corresponded exactly with the contrast extravasation on mesenteric DSA. MDCT also has a major role in the diagnosis of massive haemoptysis and haematuria. In massive haemoptysis, MDCT has proved to be of considerable value in diagnosing bronchiectasis, bronchogenic carcinoma, aspergilloma and vascular lesions. MDCT findings can suggest a specific diagnosis in 50% of patients in whom bronchoscopy findings are nondiagnostic and in 39 to 88% of patients in whom chest radiographs are nondiagnostic. MDCT can also help localize the site of bleeding in 63%–100% of patients with hemoptysis, a rate that is higher than that for bronchoscopy. In addition, bronchial and non- bronchial systemic feeder vessels can be detected at MDCT. In massive haematuria, MDCT will allow a rapid diagnosis of arteriovenous fistula and pseudoaneurysm which is critical in the preprocedural planning of any interventional procedures. In conclusion, MDCT is critically important for rapid diagnosis in patients with massive gastrointensital haemorrhage, massive haemoptysis and massive haematuria.